2006
DOI: 10.1167/6.5.7
|View full text |Cite
|
Sign up to set email alerts
|

Illusory spreading of watercolor

Abstract: The watercolor effect (WCE) is a phenomenon of long-range color assimilation occurring when a dark chromatic contour delineating a figure is flanked on the inside by a brighter chromatic contour; the brighter color spreads into the entire enclosed area. Here, we determined the optimal chromatic parameters and the cone signals supporting the WCE. To that end, we quantified the effect of color assimilation using hue cancellation as a function of hue, colorimetric purity, and cone modulation of inducing contours.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 31 publications
6
28
2
Order By: Relevance
“…A temporal presentation was ruled out to avoid the possibility of memory effects. Free viewing has been used to study the WCE in numerous previous studies [1][2][3]6,7,16,17]. Two previous studies have used durations, respectively, of 1 s [10], not too much shorter than our estimated average duration, and 150 ms to study an achromatic variant of the WCE [4].…”
Section: Methodsmentioning
confidence: 99%
“…A temporal presentation was ruled out to avoid the possibility of memory effects. Free viewing has been used to study the WCE in numerous previous studies [1][2][3]6,7,16,17]. Two previous studies have used durations, respectively, of 1 s [10], not too much shorter than our estimated average duration, and 150 ms to study an achromatic variant of the WCE [4].…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to the luminance conditions, color conditions for the watercolor effect, particularly for non-assimilative color spreading, have not been explored much. For assimilative color spreading, previous studies demonstrated that numerous color combinations produce the effect when the luminance condition is favorable (Pinna et al, 2001 ; Devinck et al, 2006a ). The magnitude of color spreading varied with color combinations: it was large when a complementary pair of colors was used and became much smaller when the same color was used for the IC and OC colors (Pinna et al, 2001 ; Devinck et al, 2006a ).…”
Section: Introductionmentioning
confidence: 99%
“…For assimilative color spreading, previous studies demonstrated that numerous color combinations produce the effect when the luminance condition is favorable (Pinna et al, 2001 ; Devinck et al, 2006a ). The magnitude of color spreading varied with color combinations: it was large when a complementary pair of colors was used and became much smaller when the same color was used for the IC and OC colors (Pinna et al, 2001 ; Devinck et al, 2006a ). Devinck et al ( 2006a ) also showed that color spreading was strong when the IC and the OC were saturated equally, and became weaker when the saturation of one contour was decreased.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Pinna et al (2001) demonstrated that several different pairs of colors can generate the coloration effect (see also Devinck et al, 2005). Specifically, Devinck et al (2006) demonstrated that the coloration effect is stronger when the chromatic contrast is larger. Thus, the coloration effect depends on a conjunction of chromatic and luminance contrasts but also on spatial parameters of the inner and outer contours.…”
Section: Figure 1 About Herementioning
confidence: 90%